ENGLISH IN THE EFL CLASSROOM: VOICES FROM INDONESIA’S PRE-SERVICE TEACHERS - Oktavia, Rani; Baehaqi, Luqman; Qamariah, Zaitun; Irawati, Dini; Sarehmasor, Tawfiq (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2025)
This study examines the views of pre-service English teachers regarding the use of English as the primary language of instruction in Indonesian EFL settings. The research is based on Krashen’s Input Hypothesis and theories related to teacher cognition, focusing on the difficulties of maintaining a balance between comprehensible input and the use of the first language as a support. Using a phenomenological approach as outlined by Moustakas (1994), the study gathered data through semi-structured interviews and classroom microteaching observations with six pre-service teachers at UIN Palangka Raya. The results identify three primary approaches: (1) full immersion in English, (2) clarification through code-switching, and (3) reliance on Indonesian for understanding. These perspectives are influenced by the participants’ previous experiences, confidence in teaching, and the practical conditions of the classroom. The research indicates that while immersion is seen as beneficial for developing language habits, the strategic use of Indonesian is still important for ensuring understanding and managing the classroom. The findings offer insights for teacher education programs in helping future teachers make appropriate and context-appropriate language choices in their instruction.